2015
DOI: 10.1210/jc.2015-1757
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Growth Hormone Treatment on Fractures and Quality of Life in Postmenopausal Osteoporosis: A 10-Year Follow-Up Study

Abstract: GH treatment was beneficial for bone and fracture outcome after 10 years but did not affect the QoL of the women with postmenopausal osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…Since GH treatment has been shown to increase both bone formation and resorption, GH therapy has not been evaluated fully to treat osteoporotic patients. Promisingly, a recent study has reported that GH therapy in postmenopausal women with osteoporosis significantly improved BMD and fracture outcomes after ten years, although overall quality of life measures were unaffected (Krantz et al, 2015). What effect this report will have on the use of GH to treat osteoporosis remains to be seen.…”
Section: Gh/igf Therapymentioning
confidence: 99%
“…Since GH treatment has been shown to increase both bone formation and resorption, GH therapy has not been evaluated fully to treat osteoporotic patients. Promisingly, a recent study has reported that GH therapy in postmenopausal women with osteoporosis significantly improved BMD and fracture outcomes after ten years, although overall quality of life measures were unaffected (Krantz et al, 2015). What effect this report will have on the use of GH to treat osteoporosis remains to be seen.…”
Section: Gh/igf Therapymentioning
confidence: 99%
“…A double‐blind, randomized placebo‐controlled study from Sweden investigated the effects of GH treatment for 3 years in postmenopausal women with osteoporosis and showed a 14% increase in BMD . In the 10‐year follow‐up study, a lasting beneficial effect on bone and fracture outcomes was observed compared with controls . Other studies found no positive effects of GH therapy on BMD.…”
Section: Discussionmentioning
confidence: 99%
“…A double-blind, randomized study conducted in Sweden by Krant et al [28] followed menopausal women with osteoporosis (n = 80) for 10 years, all undergoing estrogenic hormone replacement therapy, where one group received re-combinant GH for 36 months and the other received placebo for 18 months.…”
Section: Gh/igf-1 and Bone Mineral Densitymentioning
confidence: 99%